Violencia intrafamiliar y su influencia en el estado de ánimo de los estudiantes del Primero de Bachillerato Ciencias Básicas sección vespertina del Colegio Técnico Fiscal mixto 27 de Febrero de la ciudad de Loja, periodo 2015 - 2016. - Aguirre González, Ana Belén (2016)
This research aims to determine the existence of domestic violence and their influence on the mood of adolescents in the first bachelor of science basic technical college “27 de Febrero”, in the city of Loja; identify types of domestic violence that affects mostly adolescents; know the factors that influence domestic violence; determine the prevalence of problems in the mood that develop in the teen in an environment of domestic violence. Inductive-deductive and synthetic analytical method used in this research. To conduct the research study counted with a sample of 40 students, who are I apply a psychological test and a survey. According to the most relevant data was evidence of domestic violence, in which most adolescents report psychological violence within the home, with a lower percentage physical violence and sexual violence. It also was determined that domestic violence leads to negative consequences in adolescent mood manifesting itself most with anxiety and a lower percentage with depression. The lack of communication, cooperation, family recreation and economic problems, using insulting or abusive language, discrimination of any member of the family for the rest of the members listed as impact factors that affect mostly the household and thus affect domestic violence. So it is concluded that violence in all its forms and types, have unfortunate consequences for the emotional and psychological life of the adolescent, affecting their mood and therefore their behavior and normal development. Therefore a psychotherapeutic approach for the prevention, eradication, detection and intervention for victims of domestic violence, taking into account family factors that are directly associated with violent behavior in the home, with the sole purpose of providing knowledge, make them aware of the serious impact of violence on their children. Keywords: Domestic Violence, Adolescence, mood.